Using of Vehicle Movement to Overcome Running Out of Mobile Phone Batteries Problems - Mohamed Moheyeldin Mahmoud (African Journal of Advanced Pure and Applied Sciences, 2024)
How many times have you been exposed to an embarrassing situation or missed an opportunity, a prize or an important meeting because of your phone ran out of charge and you was not able to find an electric source or a suitable plug. As being fed up with mobile dead batteries, and as a part of the System Design Course projects taught to the third year, Faculty of Applied Arts, Beni-Suef University, Department of Industrial Design students, a team consisting of, Engy Deya William and Mohamed Khaled Mohamed, under supervision of the researcher, thought about an idea that could harness the gust of wind or aerodynamic drag resulting from a moving vehicle and the way of using the resulting, renewable source of electric energy in recharging mobile phone batteries. An experiment was conducted on a prototype and concluded that as a 20 km/h moving vehicle has the ability to generate about 3 volts, 50 mA measured by the use of a Multi-meter, and the amount of electrical energy generated is directly proportional to the speed of the vehicle, the proposed design idea is fully suitable for daily life activities and within city roads, but it may need further study to ensure its suitability on highways and at high speeds.